2019
DOI: 10.1016/j.schres.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trajectory of early functional recovery in patients with first episode psychosis

Abstract: Background: There is a large variability in the recovery trajectory and outcome of first episode of psychosis [FEP] patients. To date, individuals' outcome trajectories at early stage of illness and potential risk factors associated with a poor outcome trajectory are largely unknown. This study aims to apply three separate predictors (positive symptoms, negative symptoms, and soft neurological signs) to identify homogeneous function outcome trajectories in patients with FEP using objective data-driven methods,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 110 publications
(104 reference statements)
5
31
1
1
Order By: Relevance
“…Statistical methods like latent class growth analysis (LCGA) can help to provide a more accurate picture of the heterogeneous course in psychosocial functioning that can be observed following FEP, as it allows considering different outcomes of the same characteristic simultaneously [ 12 , 13 ]. To our knowledge, only few studies so far have applied these statistical techniques to assess functional outcomes in FEP samples [ 14 , 15 , 16 ], and none of them has considered simultaneously sociodemographic variables, clinical features and an extensive set of cognitive domains, all of them previously related to poor functional outcomes [ 17 ]. Therefore, our main aim was to identify different trajectories of functional impairment in the 24-month follow-up of a FEP cohort and to assess putative predictors of these diverse trajectories, with a special focus on resilient trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical methods like latent class growth analysis (LCGA) can help to provide a more accurate picture of the heterogeneous course in psychosocial functioning that can be observed following FEP, as it allows considering different outcomes of the same characteristic simultaneously [ 12 , 13 ]. To our knowledge, only few studies so far have applied these statistical techniques to assess functional outcomes in FEP samples [ 14 , 15 , 16 ], and none of them has considered simultaneously sociodemographic variables, clinical features and an extensive set of cognitive domains, all of them previously related to poor functional outcomes [ 17 ]. Therefore, our main aim was to identify different trajectories of functional impairment in the 24-month follow-up of a FEP cohort and to assess putative predictors of these diverse trajectories, with a special focus on resilient trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of clustering techniques and multi-channel MMN activity employed in the current study facilitates the identification of neurobiological homogeneous subgroups. In two prior studies, we have used K-means analyses and identified distinct “Bio-classes” ( 38 ) among patients and controls and unique functional trajectories ( 4 ) among FEP patients that do not respect clinical diagnosis boundaries. Within each class, individuals shared a similar neurobiological profile or functional outcome trajectories that uniquely distinguished among the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Early intervention can play a substantial role in improving long-term outcomes, although there is a large variability in treatment responsiveness in the first episode of psychosis (FEP) patients ( 3 ). FEP patients demonstrate a wide range of cognitive and neurophysiological impairments and are considerably heterogeneous in the functional outcome trajectories ( 4 6 ). Progress is undoubtedly hampered by considerable biological and clinical heterogeneity across FEP: effective treatments are unlikely to advance substantially until disease mechanisms are better understood, and biologically-based objective markers are available to tag the cardinal dysfunction, not the diagnoses or symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…A recent longitudinal study using a data-driven machine learning unsupervised approach has identified four homogeneous early function outcome trajectories in patients with first episode of psychosis. 30 Longitudinal data-driven trajectory analysis is useful because it looks beyond conventional diagnostic categories to better understand heterogeneity in the longitudinal course of psychosis syndromes and provide insight into clinically meaningful subgroups of patients. 31 Such a strategy may likely facilitate personalized approach to prediction and treatment.…”
mentioning
confidence: 99%